Recarga e flutuação do nível da água subterrânea em subbacias com floresta e campo nativo - Dambrós, Cristiane (2011)
This study aims to contribute to the investigations aimed at understanding the behavior of groundwater. With the aim of guiding the determination of groundwater recharge estimation and analysis of the fluctuation of water level in relation to meteoric precipitation events. Given the research goals relies on references: theoretical and conceptual, highlighting topics such as watershed, groundwater level fluctuation and sustainability; methodology was applied to the quantitative method in a systemic approach in two sub-basins, of a native field and the other with eucalyptus forest, which is located at the outcrop zone of the Guarani Aquifer System, at rural area of the Rosário do Sul/Rio Grande do Sul state/southern Brazil. We installed five monitoring wells and assessed the levels of groundwater for approximately two hydrological years. A well was drilled in the sub-basin of field and four wells in the sub-basin with forest. To estimate the recharge to one unconfined aquifer, used the method Water Table Fluctuation WTF. Analyses of the physical characteristics of soil and rock samples were used in detailed studies of laboratory tests related to grain size, hydraulic conductivity and porosity. For the method WTF, needed to perform the determination of the parameters: Specific Yield - Sy and the sum of the extrapolated values for each recession curve - ∆h. The results were satisfactory, and the range of the fluctuation level values between 1.36 and 4.52 meters and the estimated total groundwater recharge of precipitation in the period from 3.97% for sub-basin of the native field and 3.20% at forested sub-basin. It is concluded that studies on the recharge of an aquifer are critical for sustainable management of water resources at the local level (monitoring well) and watershed scales.